1996
DOI: 10.1111/j.1476-5381.1996.tb15378.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal 5‐HT2 receptor‐mediated facilitation of pudendal nerve reflexes in the anaesthetized cat

Abstract: 1 5-Hydroxytryptamine (5-HT) is intimately associated with central sympathetic and somatic control of the lower urinary tract. The sympathetic and somatic innervation of the lower urinary tract is conveyed through efferent axons of the hypogastric and pudendal nerves, respectively. 2 The present study examined the effects of 2,5-dimethoxy-4-iodophenylisopropylamine (DOI), a 5-HT2 receptor subtype-selective agonist, on evoked potentials recorded from the central ends of the hypogastric and pudendal nerves in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 28 publications
2
38
0
1
Order By: Relevance
“…EUS motoneurons also express PICs and appear to have comparable neuromodulatory influences (Burgard et al 2008;Paroschy and Shefchyk 2000;Rajaofetra et al 1992;Thor et al 1993;Ye et al 2009). In vivo studies of lower urinary tract function show that drugs that interact with these neuromodulatory influences alter EUS activity (Danuser and Thor 1996;de Groat et al 1990;Mbaki and Ramage 2008;Thor and Katofiasc 1995;Thor et al 2002). These observations are consistent with PICs having a role in EUS motoneuron firing behavior during urinary function.…”
Section: Expression Of Pics In Eus Motoneuronssupporting
confidence: 74%
“…EUS motoneurons also express PICs and appear to have comparable neuromodulatory influences (Burgard et al 2008;Paroschy and Shefchyk 2000;Rajaofetra et al 1992;Thor et al 1993;Ye et al 2009). In vivo studies of lower urinary tract function show that drugs that interact with these neuromodulatory influences alter EUS activity (Danuser and Thor 1996;de Groat et al 1990;Mbaki and Ramage 2008;Thor and Katofiasc 1995;Thor et al 2002). These observations are consistent with PICs having a role in EUS motoneuron firing behavior during urinary function.…”
Section: Expression Of Pics In Eus Motoneuronssupporting
confidence: 74%
“…A similar interaction between glutamatergic transmission and monoaminergic modulatory mechanisms has been proposed to explain the reflex control of the EUS motoneurons and the action of duloxetine in the cat spinal cord (7,33,35), although in this species 5-HT 2 rather than 5-HT 1A receptors are thought to be involved (8,33). The clinical efficacy of duloxetine to enhance EUS function and reduce stress urinary incontinence (33) suggests that monoaminergic-glutamatergic interactions may be important for promoting urinary continence in humans.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT enhances the guarding reflex by binding to 5-HT 2 receptors in rats and cats (8,24). Autoradiographic staining of spinal cord sections revealed high density of 5-HT 2 receptors in Onuf's nucleus but few receptors in the surrounding ventral horn (25).…”
Section: Effects Of Intrathecal Application Of Way-100635 and Rs-10mentioning
confidence: 99%
“…Moreover, 5-HT receptors are divided into seven families (5-HT 1-7 ) (24). Among them, it is well-known that 5-HT 2 receptor stimulation activates the pudendal nerve to increase external urethral sphincter activity in cats, guinea pigs, and rats (8,9,24). It has also been reported that 5-HT 1A receptor activation can enhance external urethral sphincter activity in rats and cats (6,7,27).…”
mentioning
confidence: 99%